Anesthesiology Resident Night Float Duty Alters Sleep Patterns: An Observational Study. (August 2019) - Dunn, Lauren K.; Kleiman, Amanda M.; Forkin, Katherine T.; Bechtel, Allison J.; Collins, Stephen R.; Potter, Jennifer F.; Kaperak, Christopher J.; Tsang, Siny; Huffmyer, Julie L.; Nemergut, Edward C.
Editor's Perspective: What We Already Know about This Topic: Night float is one mechanism for fulfilling resident call responsibilities while avoiding prolonged clinical care that violates duty hours What This Article Tells Us That Is New: In anesthesiology residents conducting six consecutive nights of clinical care, three nights of recovery did not appear to restore normal sleep architecture, raising questions about this practice Background: Residency programs utilize night float systems to adhere to duty hour restrictions; however, the influence of night float on resident sleep has not been described. The study aim was to determine the influence of night float on resident sleep patterns and quality of sleep. We hypothesized that total sleep time decreases during night float, increases as residents acclimate to night shift work, and returns to baseline during recovery. Methods: This was a single-center observational study of 30 anesthesia residents scheduled to complete six consecutive night float shifts. Electroencephalography sleep patterns were recorded during baseline (three nights), night float (six nights), and recovery (three nights) using the ZMachine Insight monitor (General Sleep Corporation, USA). Total sleep time; light, deep, and rapid eye movement sleep; sleep efficiency; latency to persistent sleep; and wake after sleep onset were observed. Results: Mean total sleep time ± SD was 5.9 ± 1.9 h (3.0 ± 1.2.1 h light; 1.4 ± 0.6 h deep; 1.6 ± 0.7 h rapid eye movement) at baseline. During night float, mean total sleep time was 4.5 ± 1.8 h (1.4-h decrease, 95% CI: 0.9 to 1.9, Cohen's d = –1.1, P < 0.001) with decreases in light (2.2 ± 1.1 h, 0.7-h decrease, 95% CI: 0.4 to 1.1, d = –1.0, P < 0.001), deep (1.1 ± 0.7 h, 0.3-h decrease, 95% CI: 0.1 to 0.4, d = –0.5, P = 0.005), and rapid eye movement sleep (1.2 ± 0.6 h, 0.4-h decrease, 95% CI: 0.3 to 0.6, d = –0.9, P < 0.001). Mean total sleep time during recovery was 5.4 ± 2.2 h, which did not differ significantly from baseline; however, deep (1.0 ± 0.6 h, 0.4-h decrease, 95% CI: 0.2 to 0.6, d = –0.6, P = 0.001 *, P = 0.001) and rapid eye movement sleep (1.2 ± 0.8 h, 0.4-h decrease, 95% CI: 0.2 to 0.6, d = –0.9, P < 0.001 P < 0.001) were significantly decreased. Conclusions: Electroencephalography monitoring demonstrates that sleep quantity is decreased during six consecutive night float shifts. A 3-day period of recovery is insufficient for restorative sleep (rapid eye movement and deep sleep) levels to return to baseline. Abstract : In anesthesiology residents conducting six consecutive nights of clinical care, three nights of recovery did not appear to restore normal sleep architecture, raising questions about this practice.Supplemental Digital Content is available in the text.